UNRAVELLING THE IMPACT OF RELIGIOUS THERAPY ON STRESS BIOMARKERS IN ICU PATIENTS - A TRUE EXPERIMENTAL STUDY - Purnawan, Iwan; Hidayat, Arif Imam; Awaludin, Sidik; Alivian, Galih Noor; Sutrisna, Eman; Wirakhmi, Ikit Netra (Universitas Aisyah Pringsewu, 2023)
Elevated stress biomarkers, such as cortisol, in response to stress conditions, can impede the healing process, prolong hospitalization, and escalate healthcare costs. This research examines the influence of religious therapy on cortisol levels in Intensive Care Unit (ICU) patients. Employing a true experimental design, 40 ICU patients were randomly assigned to the intervention or control group, comprising 20 participants each. Salivary cortisol samples were collected before and after the intervention and analyzed using the ASSAY method.The intervention group received religious therapy consisting of 15-minute sessions of listening to Quranic recitations, while the control group received no treatment. Statistical analysis involved an independent t-test to assess mean differences in cortisol level reduction between the two groups. Homogeneity testing confirmed that both groups had similar demographic characteristics regarding gender and age (p 0.05).The results showed a significant difference in mean cortisol level reduction between the intervention group (16.3 + 25.3 ng/ml) and the control group (-0.4 + 18.2 ng/ml) (p = 0.021). Additionally, Cohen's d-test indicated a substantial effect size of 0.71, highlighting the notable impact of religious therapy on cortisol level reduction. In conclusion, religious therapy effectively reduced cortisol levels among critically ill patients in the ICU.